Mushroom in livelihood system of rural women - Mishra, Sabita (Mushroom Research, 2012)
This study was conducted in Khurda district of Odisha. Seventy-five farm women were purposefully selected who were exposed with training and demonstration on mushroom cultivation. The data were collected with the help of structured schedule developed on the basis of objectives. The collected data were statistically processed. The study reveals that the most important promoting factor for mushroom enterprise is simple technology, which farmwomen can handle very easily. The impact assessment of mushroom enterprise on growers indicates the improvement in their occupation (53.33%) followed by â€˜standard of livingâ€™ (36.00%), â€˜savingâ€™ (30.00%), employment generation (26.66%) and â€˜knowledge and attitudeâ€™ (24%). The farmwomen faced much constraint in â€˜non-availability of spawn in localityâ€™ and least problem in â€˜mushroom treated as non-veg itemâ€™. Sixty percent of the respondents stated that â€œsupply of quality spawnâ€, â€˜thorough coverage of marketing aspectsâ€™ and â€˜insuranceâ€™ are the three major constraints for successful mushroom entrepreneurship.Â